2009
DOI: 10.1177/0272989x09347016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5 Health-Related Quality-of-Life Indexes Using Item Response Theory Analysis

Abstract: Background-Five health-related quality-of-life (HRQoL) indexes-EQ-5D, HUI2, HUI3, QWB-SA, and SF-6D-are each used to assign community-based utility scores to health states, although these scores differ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 16 publications
3
82
0
Order By: Relevance
“…These findings corroborate with other studies that have indicated non-linear relationships across HSU-instruments [8,9,11]. Scaling effect could be key factor to explain the observed nonlinear relationship [3,20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings corroborate with other studies that have indicated non-linear relationships across HSU-instruments [8,9,11]. Scaling effect could be key factor to explain the observed nonlinear relationship [3,20].…”
Section: Discussionsupporting
confidence: 92%
“…Crosswalks or 'mappings' between a disease specific instrument and a HSU-instruments are commonly used to enable QALY estimations [6,7]. However, while such crosswalks between HSU-instruments are rare [8][9][10][11], previous studies have indicated non-linear relationships [8,9,11]. By the use of item response analysis, Fryback and colleagues investigated the interrelationship of five instruments (EQ-5D-3L, HUI2, HUI3, QWB-SA, SF-6D) in a sample of US adults (N=3844).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A weaker association was found compared to results in Australia (reflecting the use of only general population respondents). Overall, 53% of instrument variance was not explained 7 .…”
Section: Rheumatologymentioning
confidence: 90%
“…While Drasgow and colleagues developed this approach in the context of largescale educational testing applications (N) 10,000), others have recently used the X2/dj ratio index of model fit in studies examining such diverse issues as health-related quality of life (Fryback, Palta, Cherepanov, Bolt, & Kim, 2010); attention-deficit hyperactivity disorder in children (Gomez, 2008); cultural equivalence of measures of depression (Kim, Chiriboga, & Jang, 2009); forensic psychopathy (Bolt, Hare, & Neumann, 2007); spiritual wellbeing (Gomez & Fisher, 2005); business leadership (Zagorsek, Stough, & Jaklic, 2006); financial risk-taking (Lampenius & Zickar, 2005); emotional intelligence (Cooper & Petrides, 2010); sexual harassment in the military (Estrada, Probst, Brown, & Graso, 2011;Stark, Chernyshenko, Lancaster, Drasgow, & Fitzgerald, 2002); military attrition (Stark, Chernyshenko, Drasgow, Lee, White, & Young, 2011); and personality assessment (Chernyshenko, Stark, Chan, Drasgow, & Williams, 2001;Maydeu-Olivares, 2005;Robie, Zickar, & Schmit, 2001;Schmidt, Kihm, & Robie, 2000;Zickar & Drasgow, 1996). Sample sizes in these investigations ranged from under 300 (Lampenius & Zickar, 2005) to nearly 72,000 (Estrada et aI., 2011), illustrating the multitude of settings and designs characterizing current applied research utilizing IRT methods.…”
Section: Introductionmentioning
confidence: 99%